2020
DOI: 10.32890/jis2020.16.8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Trend and Sources of Government Budget Deficit Financing in Bangladesh

Abstract: Budget deficit is one of the most significant macroeconomic issues which have been debated both in the academic and political arena since 1970s. This study aims to explore the current position of government budget deficit, its trends, and sources of budget deficit financing in Bangladesh covering the periods of 1980 to 2018. Secondary data has been used which is collected from Bangladesh Economic Review and World Bank. Data has been analyzed through descriptive methods. The Government financing budget deficit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In addition, money supply, national debt, and international trade also significantly impacted the short and long term fiscal deficit. Sadekin et al (2020), using trend analysis for Bangladesh, found that government financing is a significant determinant of fiscal deficit. Alam et al (2020), using a VECM approach, found that inflation, exchange rate, trade, and money supply had a negative effect on fiscal deficit in the short run but a positive association in the long run.…”
Section: Empirical Literaturementioning
confidence: 99%
“…In addition, money supply, national debt, and international trade also significantly impacted the short and long term fiscal deficit. Sadekin et al (2020), using trend analysis for Bangladesh, found that government financing is a significant determinant of fiscal deficit. Alam et al (2020), using a VECM approach, found that inflation, exchange rate, trade, and money supply had a negative effect on fiscal deficit in the short run but a positive association in the long run.…”
Section: Empirical Literaturementioning
confidence: 99%
“…External shocks, debt ratios, financial development, democracy, and government spending control are all strongly linked to fiscal deficits, according to the researchers' findings. Sadekin et al (2020) investigates the patterns and origins of Bangladesh's government budget deficit. The data was analysed using descriptive techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many state-owned enterprises (SOEs) in developing and transition economies, including South Africa, are loss-making and inefficient, burdening government finances and scarce resources. Their poor financial performance affects service delivery and their ability to fulfill the government's growth and developmental objectives (Sadekin et al, 2020;Billio et al, 2021). The question dominating discussion is: How does the capital structure of South African SOEs affect their financial performance with and without government support?…”
Section: Introductionmentioning
confidence: 99%